A Dose-ranging Study of the Oral Direct Thrombin Inhibitor, Ximelagatran, and Its Subcutaneous Form, Melagatran, Compared with Dalteparin in the Prophylaxis of Thromboembolism after Hip or Knee Replacement: METHRO I - Eriksson, Bengt I.; Arfwidsson, Ann-Christin; Frison, Lars; Eriksson, Ulf G.; Bylock, Anders; Kälebo, Peter; Fager, Gunnar; Gustafsson, David (Thrombosis and Haemostasis, 2002)
The novel, oral direct thrombin inhibitor, ximelagatran (formerly H 376/95), represents an advance in antithrombotic therapy through its oral availability. After oral administration, ximelagatran is converted to its active form, melagatran. Melagatran can also be administered subcutaneously (sc). The results from the first clinical study with ximelagatran are reported. In this randomized, parallel-group, controlled study, 103 patients scheduled for elective total hip or total knee replacement received sc melagatran (1, 2 or 4 mg bid) for 2 days commencing immediately before surgery, followed by oral ximelagatran (6, 12 or 24 mg bid) for 6-9 days. Another 33 patients received dalteparin 5000 IU sc once daily, started the evening before surgery, for 8-11 days. At bilateral venography, deep vein thrombosis was found in 20.5% (16/78) of patients who had received sc melagatran and oral ximelagatran and in 18.5% (5/27) of patients in the dalteparin group. The study did not evaluate a dose-response for efficacy, and no differences between the three dose levels of melagatran and ximelagatran were shown. No pulmonary embolism was diagnosed during treatment. Total bleeding in the sc melagatran plus oral ximelagatran groups showed no dose-response and was similar to that seen in the dalteparin group. The pharmacokinetic properties of melagatran in the surgery patients were consistent with those observed for healthy subjects, and the APTT ratio, which increased non-linearly with plasma melagatran concentration, showed a consistent concentration-effect relationship during the treatment period. Ximelagatran and melagatran were well tolerated. In conclusion, ximelagatran and its active form melagatran appear to be promising agents for the prevention of venous thromboembolism following orthopaedic surgery.
Keywords: Deep vein thrombosis; thrombin inhibitors; melagatran; ximelagatran; H 376/95; oral direct thrombin inhibition